2005
DOI: 10.1161/01.cir.0000155242.70417.60
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Restenosis and Health Status Outcomes for Patients Undergoing Percutaneous Coronary Intervention Versus Coronary Artery Bypass Graft Surgery

Abstract: Background-Previous

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 35 publications
(22 reference statements)
1
27
0
1
Order By: Relevance
“…4 Predictive restenosis risk stratification models might be helpful for identifying patients who may preferentially benefit from surgery compared with stenting. 9,10 This is of particular importance because only a minority of patients without apparent in-stent restenosis at 6-month follow-up will require subsequent target vessel revascularization. 11 The indication for repeated revascularization procedures was clinically and not angiographically driven.…”
Section: Discussionmentioning
confidence: 99%
“…4 Predictive restenosis risk stratification models might be helpful for identifying patients who may preferentially benefit from surgery compared with stenting. 9,10 This is of particular importance because only a minority of patients without apparent in-stent restenosis at 6-month follow-up will require subsequent target vessel revascularization. 11 The indication for repeated revascularization procedures was clinically and not angiographically driven.…”
Section: Discussionmentioning
confidence: 99%
“…8 -10 However, several key predictors-younger patient age, performance of unprotected left main PCI, and SVG location-have not been reported consistently in prior models. One single-center analysis of bare metal stents by Spertus et al 8 identified age Ͻ55 years as a predictor of restenosis, but several more recent DES studies have not reported this finding. 10,11 Left main PCI was much less likely to be undertaken before widespread acceptance of DES and therefore was unlikely to have been adequately represented in prior observational registries to be identified as a TLR risk factor.…”
Section: Comparison With Previous Studiesmentioning
confidence: 99%
“…To better identify patients at higher risk of restenosis, several investigators have developed risk-prediction models based on clinical and angiographic variables associated with target lesion revascularization (TLR). However, these models were developed before widespread availability of DES, 8,9 in singlecenter experiences, 10,11 or in restrictive patient subsets. 4 In addition, none of the predictors identified in DES populations have undergone independent validation.…”
mentioning
confidence: 99%
“…Moreover, a systematic evaluation of the psychological burden of undergoing multiple stent procedures over time is lacking, and only limited information exists about the quality of life of these patients. 18 Finally, the cost-effectiveness of multiple PCI procedures compared with CABG has to be questioned.…”
Section: Limitationsmentioning
confidence: 99%